The Impact of Cloud Transformation, Cyber SecurityIntegration, and 5G Adoption on Business NetworkPerformance - Shoaib Faruqi; Izza Fatima; Muhammad Azhar Mushtaq; Mohsin Saleemi; Sadaqat Ali Ramay; Hina Saleem; Maria Faheem (Spectrum of Engineering Sciences, 2025)
In today’s fast-paced digital economy, businesses increasingly rely on Cloud Transformation, Cyber Security Integration, and 5G Adoption to enhance Business Network Performance and maintain competitive advantage. This study examines how these three factors contribute to business efficiency, security, and digital scalability across enterprises in North America, Europe, and the Middle East. A quantitative research methodology was employed; utilizing a structured questionnaire distributed to 300 businesses and IT professionals specializing in network/cloud transformations and Cyber Security. The study applies statistical analysis to assess the relationship between Cloud Transformation, Cyber Security Integration, and 5G Adoption (IVs) and Business Network Performance (DV). Findings indicate that Cloud Transformation enhances business agility and operational scalability, enabling organizations to streamline processes and reduce infrastructure costs. Cyber Security Integration plays a vital role in safeguarding business data, ensuring regulatory compliance, and protecting enterprises from cyber threats. Additionally, 5G Adoption accelerates business communications, improves network reliability, and supports advanced digital operations. The study underscores the importance of a strategic, technology-driven approach to business network transformation, ensuring long-term success in an increasingly connected and data-driven global market. The insights derived provide valuable recommendations for business leaders and policymakers in designing resilient, secure, and high-performance business network infrastructures.